Straregi Komunikasi Dakwah TvmuStudi Deskriptif KualitatifDirektur Televisi Muhammadiyah - Badranana, Badranana; , Budi Santoso, S.Sos, M.Si (2017)
"The existence of TVMU will test the existence of Muhammadiyah leaders" especially TVMU directors in doing da'wah, although the previous vision of TVMU with the existing day remains the same, but the development of capital-intensive television business, does not rule out a shift of paradigm of dakwah, so that ultimately will risk the existence of the leaders and TVMU creators in dakwah.Therefore the purpose of this study was to know the steps and efforts of the director of TVMU in maintaining the existence of TVMU as a dakwah media, as well as issues and solutions.This research applied qualitative descriptive method with the length of research from January to April 2016 employing three informants; executive director of TVMU, the director of TVMU business development program and TVMU president director.This study used the case approach that occurs on TVMU related to the existence of their dakwah.The method of collecting data in this study used the type of semi-structured interview with data processing based on the acquisition of data from field notes, then were reduced, described, analyzed, then interpreted.The result of this research was the director of TVMU presented programs that deliver the message of dakwah with packaging that was more intelligent, so that all programs broadcast also could be accepted by TVMU viewers with a positive response as well.In addition, in presenting programs that carried the concept of developed Islamic dakwah, Muhammadiyah central board also appealed all leaders of tens thousands of Muhammadiyah business to access TVMU and took part in financing TVMU until it was able to run its programs independently.Muhammadiyah Central Executive Board also appealed to all PDM (muhammadiyah Regional Leaders), PCM (Head of Muhammadiyah branch), PWM (Head of Muhammadiyah region) to be able to access Muhammadiyah television.